2020
DOI: 10.1101/gr.260463.119
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the regulatory activity and sequence content of loci with exceptional numbers of transcription factor associations

Abstract: Service Email Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article-sign up in the box at the http://genome.cshlp.org/subscriptions

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 60 publications
2
17
0
Order By: Relevance
“…In previous studies, thousands of high-occupancy targets to which many different TFs bound were highlighted in mammalian genomes [ 44 , 45 ]. While this observation has partly been attributed to technical ChIP artifacts at highly expressed genes and GC-rich loci [ 46 , 47 ], recent studies suggest that this binding phenomenon is not an artifact and is based on direct TF-DNA interactions [ 48 , 49 ]. A major point of contention is the finding that many TF binding sites do not match known consensus motifs [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, thousands of high-occupancy targets to which many different TFs bound were highlighted in mammalian genomes [ 44 , 45 ]. While this observation has partly been attributed to technical ChIP artifacts at highly expressed genes and GC-rich loci [ 46 , 47 ], recent studies suggest that this binding phenomenon is not an artifact and is based on direct TF-DNA interactions [ 48 , 49 ]. A major point of contention is the finding that many TF binding sites do not match known consensus motifs [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Next, we investigated potential mechanisms that could explain how individual aSEs are able to anchor such a large number of TFs and co-activators. Previous analysis of HOT loci in individual cell lines suggest that higher GC contents may contribute to the increase in TF binding affinity at these sites ( 26 , 27 , 32 ). However, we did not detect a consistent increase in GC contents or CpG islands in aSE and dSE peaks compared to those for cSEs and rEhs ( Supplementary Figure S3A-B ), even though aSEs and dSEs associate with significantly broader and stronger DNase-seq peaks compared to cSEs and rEhs across the five cell lines (Figure 2A , Supplementary Figures S2A, S3C ).…”
Section: Resultsmentioning
confidence: 99%
“…While some studies posited this phenomenon as technical artifacts caused by high DNA accessibility or GC-rich sequences ( 32 , 33 ), increasing evidence indicates that the HOT sites are functional genomic loci that drive the transcription of highly expressed, functionally important target genes ( 26–30 ). Notably, the majority of HOT sites fall outside the classically defined SE regions ( 27 ), suggesting that distinct mechanisms and factors likely drive the trans -assembly of mega transcriptional complexes at these stand-alone sites.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, single molecule footprinting assays have indicated that co-occupancy of enhancers by several TFs increases nucleosome depletion and suggested that accessible DNA more than motif orientation and physical interaction of TFs dictates how numerous TFs stably engage enhancers in a cooperative manner [14]. However, how much individual TFs contribute to gene expression regulation is highly variable and discriminating between non-functional opportunistic TF binding versus readily functional TF recruitment at different regulatory sites has unfortunately remained difficult and controversial [15][16][17]. We envision that further technological developments and pluridisciplinary approaches involving genome editing, single-cell and single molecule analyses, high sensitivity mass-spectrometry together with machine-learning approaches should allow to overcome some of the long-standing limitations which have hindered our understanding of the TF-chromatin functional interactions.…”
Section: Mutual Influence Between Tfs and Chromatin As The Key Rule Driving Transcriptional Regulatory Eventsmentioning
confidence: 99%